COMPARATIVE EVALUATION OF TWO DIFFERENT OBTURATING SYSTEM USING CBCT AND IOPA” – AN INVIVO STUDY (CAHIERS MAGELLANES-NS, 2024)
AIM- The aim of this study was to compare & evaluate the quality of two different Obturation technique using Cone Beam Computed Tomography & Intraoral Periapical Radiograph.METHODOLOGY- This is an original in-vivo research that will be conducted in department of Conservative Dentistry and Endodontics, Jaipur at NIMS DENTAL COLLEGE. The consent from the patients and ethical board will be obtained for the procedure. Forty patients were selected. Access cavity preparation done and the patients was split into two groups (20 patients) for obturation, with Obtura II System and Thermafil system after cleaning and Shaping of the canal. Voids and Pain-perception is being checked for the quality of the obturation. To evaluate, voids present in Thermafil & Obtura II, CBCT and IOPA are used.RESULTS- After evaluating both the obturation techniques, results showed less number of voids after obturation with Thermafil technique compared to Obtura II, also patients reported higher rate of discomfort with Obtura II technique compared to Thermafil.CONCLUSION- Provided the limitations of the study, it concluded that CBCT evaluation showed Thermafil a better obturation technique compared to Obtura II and how three-dimensional imaging overcomes the limitations of conventional radiography.